A potentiometric resolved photoelectrochemical system based on CdS nanowires and SnNb2O6 nanosheets: a case application for dual biomarker analysis. Issue 10 (10th January 2020) - Cao, Jun-Tao; Ma, Yan; Lv, Jing-Lu; Ren, Shu-Wei; Liu, Yan-Ming
Abstract : A potentiometric-resolved PEC immunosensor was developed for dual-target detection. Abstract : A potentiometric resolved photoelectrochemical (PEC) system based on CdS nanowires and SnNb2 O6 nanosheets was developed. To prove the applicability of this system in PEC multi-biomarker analysis, a label free PEC immunosensor for two cardiac biomarkers, myoglobin and cardiac troponin I, was constructed.